2021
DOI: 10.7860/jcdr/2021/49411.15237
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Oxygen Saturation Index and Oxygenation Index in Hypoxaemic Respiratory Failure among Neonates

Abstract: Introduction: Hypoxaemic Respiratory Failure (HRF) is severe arterial hypoxaemia that is refractory to supplemental oxygen. Oxygen Saturation Index (OSI) can be an alternate method of diagnosing and assessing the severity of HRF as it uses Oxygen Saturation (SpO2) in place of Partial Pressure of Oxygen (PaO2) and may be utilised with reasonable sensitivity and specificity. Aim: To evaluate the correlation between OSI and Oxygenation Index (OI) in HRF in neonates. Materials and Methods: The prospective observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These results are consistent with a prospective study of Sunil and Nithya (2021) conducted in similar settings that recruited both preterm and term in study group and each selected newborns only one paired OI and OSI measurement was evaluated. Sunil and Nithya conducted a study involving 50 neonates, both term and preterm, and reported a positive correlation between OSI and OI (p-value < 0.01) [ 9 ]. The correlation coefficient (r) was found to be 0.727, which aligns with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with a prospective study of Sunil and Nithya (2021) conducted in similar settings that recruited both preterm and term in study group and each selected newborns only one paired OI and OSI measurement was evaluated. Sunil and Nithya conducted a study involving 50 neonates, both term and preterm, and reported a positive correlation between OSI and OI (p-value < 0.01) [ 9 ]. The correlation coefficient (r) was found to be 0.727, which aligns with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the AUC was 0.912, indicating a good overall accuracy of the test. These findings suggest that OSI can be used with good accuracy as a substitute for OI in assessing the severity of respiratory failure in neonates [ 9 ]. Besides, Devleta et al (2018) also observed a correlation between mean values of OSI and OI in their study involving 101 ventilated neonates those similar mean of gestational age with participants our study, with a Pearson’s coefficient of 0.76 (p < 0.0001, 95% CI = 0.66–0.83) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%